THE EFFECT OF MINERALS ON THE NUMBER OF E. coli AND COLIFORM BACTERIA IN BALI CATTLE IN THE HIGHLANDS AND LOWLANDS - Dewantari, Nyoman Rizky Agustria; Besung, I Nengah Kerta; Sampurna, I Putu (Buletin Veteriner Udayana; Vol. 8 No. 1 Pebruari 2016, 2016)
Research has been conducted to know the effect of mineral supplementation on bacterial counts of Escherichia coli (E,coli) and coliform on bali cattle raised in the highlands and lowlands.A total of 24 males bali cattle aged of 10-12 month were used in this research. The cattle wasplaced on highland and lowland, and receiving mineral spplemntation for a period of 3 months. The doses are: 2.5 g/head/ day, 5 g/head/day, and 7,5 g/head/day. The last unsupplemented group wastreated as the control. Faecal samples were obtained and grown on a culture medium by spread method to calculated the number of E.coli and coliform bacteria present in the sample. Data were analyzed using analysis of variance. The mean number of E.coli in bali cattle reared in highlands and lowlands of was 4.69771 cfu/g feaces and coliform at 5.0735 cfu/g feaces. The results showed that the mineral supplementation did not significantly affect the amount of E.coli and coliform bacteria in Bali cattle either reared in the highlands or lowlands
Keywords: bali cattle; highlands and lowlands; mineral; E. coli and coliform